Group choreography: mechanisms orchestrating the collective movement of border cells - Montell, Denise J. (2012)
Cell movements are essential for animal development and homeostasis but also contribute to disease. Moving cells typically extend protrusions towards a chemoattractant, adhere to the substrate, contract and detach at the rear. It is less clear how cells that migrate in interconnected groups in vivo coordinate their behaviour and navigate through natural environments. The border cells of the Drosophila melanogaster ovary have emerged as an excellent model for the study of collective cell movement, aided by innovative genetic, live imaging, and photomanipulation techniques. Here we provide an overview of the molecular choreography of border cells and its more general implications.